3D printed Sr-containing composite scaffolds: Effect of structural design and material formulation towards new strategies for bone tissue engineering. (3rd May 2020) - Pierantozzi, Daniele; Scalzone, Annachiara; Jindal, Swati; Stīpniece, Līga; Šalma-Ancāne, Kristīne; Dalgarno, Kenny; Gentile, Piergiorgio; Mancuso, Elena
Abstract: The use of composite materials, processed as 3D tissue-like scaffolds, has been widely investigated as a promising strategy for bone tissue engineering applications. Also, additive manufacturing technologies such as fused deposition modelling (FDM) have greatly contributed to the manufacture of patient-specific scaffolds with predefined pore structures and intricate geometries. However, conventional FDM techniques require the use of materials exclusively in the form of filaments, which in order to produce composite scaffolds lead to additional costs for the fabrication of precursor filaments as well as multi-step production methods. In this study, we propose the use of an advantageous extrusion-based printing technology, which provides the opportunity to easily co-print biomaterials, starting from their raw forms, and by using a single-step manufacturing and solvent-free process. Poly(e-caprolactone) (PCL), an FDA approved biodegradable material, was used as polymeric matrix while hydroxyapatite (HA) and strontium substituted HA (SrHA), at various contents were introduced as a bioactive reinforcing phase capable of mimicking the mineral phase of natural bone. Three different architectures for each material formulation were designed, and subsequently the effect of composition variations and structural designs was analysed in terms of physico-chemical, mechanical and biological performance. A correlation between architecture and compressive modulus, regardless the formulation tested, was observed demonstrating how the laydown pattern influences the resulting 3D printed scaffolds' stiffness. Furthermore, in vitro cell culture by using TERT Human Mesenchymal Stromal Cells (hTERT-MSCs) revealed that Sr-containing composite scaffolds showed greater levels of mineralisation and osteogenic potential in comparison to bare PCL and pure HA.